You need to remember the form of equation of tangent line to the graph of function at a point `x=a` such that:

`g(x)- g(a) = g'(a)(x-a)`

Notice that the problem does not provide the equation of function, but it provides the values of `g(x) ` and `g'(x)` at `x =6` such that:

`g(x) - g(6) = g'(6)(x-6)`

Substituting -3 for `g(6)` and 2 for `g'(6)` yields:

`g(x) -(-3) = 2(x-6) => g(x) + 3 = 2x - 12`

Substituting y for g(x) yields:

`y = 2x - 12 - 3 => y = 2x - 15`

**Hence, evaluating the equation of the tangent line to the graph of the function g(x), at x = 6, yields `y = 2x - 15.` **

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now